Peran Guru Pendidikan Agama Islam dalam Meningkatkan Akhlak Peserta Didik: The Role of Islamic Religious Education Teachers in Improving Students' Morals - Ayu Parcelia, Febi; Mariska, Revi; Nadenha Putri, Septi; Agustia Almirah, Zahra; Sukawati (CV. Kalimasada Group, 2024)
A teacher plays a role in developing the morals of his students, to fulfill his responsibilities as an educator a teacher also has the requirements to become a teacher, competence and professionalism in his field, and knowing his duties and responsibilities as an educator, conveying theories about morals is not enough to make students understand about moral education itself. Therefore a teacher carries out his role as an educator to foster the morals of his students so that they have good personalities and noble morals. The problem in this study is the role of Islamic Education teachers in improving the morals of students. The type of research conducted is qualitative research, using data collection approaches such as interviews, observations, and documentation. In this study, samples were taken from class IX students at Smpn 1 Sungkai Utara. From the research conducted, through observations and interviews conducted, it can be seen that Islamic religious teachers play a role in fostering the morals of their students. This is manifested in the implementation of Islamic religious teaching, including in the teaching and learning process, teachers deliver material with various methods of providing motivation to students. The morals of students at this school can be said to be quite good. by always having good morals, including being honest and respecting parents and teachers. However, some of them still have bad morals, including taking things that are not theirs, speaking loudly to older people